The chemistry of the actinide and transactinide elements. Volumes 1-6 - Morss, Lester R.; Edelstein, Norman M. 1936-.; Fuger, Jean.; SpringerLink (Online service). (Dordrecht Springer Netherlands, 2010)
The Chemistry of the Actinide and Transactinide Elements is the contemporary and definitive exposition of chemical properties of all of the actinide elements, especially of the technologically important elements uranium and plutonium, as well as the transactinide elements. In addition to the comprehensive treatment of the chemical properties of each element, ions and compounds from atomic number 89 (actinium) through 109 (meitnerium), the multi-volume work has specialized and authoritative chapters on electronic theory, optical and laser fluorescence spectroscopy, X-ray absorption spectroscopy, organoactinide chemistry, thermodynamics, magnetic properties, the metals, coordination chemistry, separations, trace analysis. The Editors invited teams of authors, who are active practitioners and recognized experts in their specialty, to write each chapter and have endeavored to provide a balanced and insightful treatment of these fascinating elements at the frontier of the periodic table. Because the field has expanded with new spectroscopic techniques and environmental focus, the work now encompasses six volumes. All chapters represent the current state of research in the chemistry of these elements and related fields. - Publisher's description.
Volume 1: 1. Introduction (Joseph J. Katz, Lester R. Morss, Norman M. Edelstein and Jean Fuger) 2. Actinium (H. W. Kirby and L. R. Morss) 3. Thorium (Mathias S. Wickleder, Blandine Fourest, and Peter K. Dorhout) 4. Protactinium (Boris F. Myasoedov, H. W. Kirby, and Ivan G. Tananaev) 5. Uranium (Ingmar Grenthe, Janusz Drożdżyński, Takeo Fujino, Edgar C. Buck, Thomas E. Albrecht-Schmitt, and Stephen F. Wolf); Volume 2: 6. Neptunium (Zenko Yoshida, Stephen G. Johnson, Takaumi Kimura, and John R. Krsul) 7. Plutonium (David L. Clark, Siegfried S. Hecker, Gordon D. Jarvinen, and Mary P. Neu) 8. Americium (Wolfgang H. Runde and Wallace W. Schulz); Volume 3: 9. Curium (Gregg J. Lumetta, Major C. Thompson, Robert A. Penneman, and P. Gary Eller) 10. Berkelium (David E. Hobart and Joseph R. Peterson) 11. Californium (Richard G. Haire) 12. Einsteinium (Richard G. Haire) 13. Fermium, Mendelevium, Nobelium, and Lawrencium (Robert J. Silva) 14. Transactinide Elements and Future Elements (Darleane C. Hoffman, Diana M. Lee, and Valeria Pershina) 15. Summary and Comparison of Properties of the Actinide and Transactinide Elements (Norman M. Edelstein, Jean Fuger, Joseph J. Katz, and Lester R. Morss) 16. Spectra and Electronic Structures of Free Actinide Atoms and Ions (Earl F. Worden, Jean Blaise, Mark Fred, Norbert Trautmann, and Jean-François Wyart) 17. Theoretical Studies of the Electronic Structure of Compounds of the Actinide Elements (Nikolas Kaltsoyannis, P. Jeffrey Hay, Jun Li, Jean-Philippe Blaudeau, and Bruce E. Bursten) 18. Optical Spectra and Electronic Structure (Guokui Liu and James V. Beitz); Volume 4: 19. Thermodynamic Properties of Actinides and Actinide Compounds (Rudy J. M. Konings, Lester R. Morss, and Jean Fuger) 20. Magnetic Properties (Norman M. Edelstein and Gerard H. Lander) 21. 5f-Electron Phenomena in the Metallic State (A. J. Arko, John J. Joyce, and Ladia Havela) 22. Actinide Structural Chemistry (Keith E. Gutowski, Nicholas J. Bridges, and Robin D. Rogers) 23. Actinides in Solution: Complexation and Kinetics (Gregory R. Choppin and Mark P. Jensen) 24. Actinide Separation Science and Technology (Kenneth L. Nash, Charles Madic, Jagdish N. Mathur, and Jérôme Lacquement); Volume 5: 25. Organoactinide Chemistry: Synthesis and Characterization (Carol J. Burns and Moris S. Eisen) 26. Homogeneous and Heterogeneous Catalytic Processes Promoted by Organoactinides (Carol J. Burns and Moris S. Eisen) 27. Identification and Speciation of Actinides in the Environment (Claude Degueldre) 28. X-ray Absorption Spectroscopy of the Actinides (Mark R. Antonio and Lynda Soderholm) 29. Handling, Storage, and Disposition of Plutonium and Uranium (John M. Haschke and Jerry L. Stakebake) 30. Trace Analysis of Actinides in Geological, Environmental, and Biological Matrices (Stephen F. Wolf) 31. Actinides in Animals and Man (Patricia W. Durbin) Appendix I: Nuclear Spins and Moments of the Actinides (Irshad Ahmad) Appendix II: Nuclear Properties of Actinide and Transactinide Nuclides (Irshad Ahmad); Volume 6: 32. Actinides in the Geosphere (Wolfgang Runde and Mary P. Neu) 33. Subsurface Interactions of Actinide Species with Microorganisms (Donald T. Reed, Randhir P. Deo, and Bruce E. Rittmann) 34. Nuclear Fuels (Rudy J. M. Konings, Thierry Wiss, and Christine Guéneau) 35. Actinide Waste Forms and Radiation Effects (R. C. Ewing and W. J. Weber) 36. Analytical Chemistry of Plutonium (Kenton J. Moody, Dawn A. Shaughnessy, Karin Casteleyn, Herbert Ottmar, Klaus Lützenkirchen, Maria Wallenius, and Thierry Wiss) 37. Actinide Chalcogenide Compounds (Emmanouil Manos, Mercouri G. Kanatzidis, and James A. Ibers) 38. Molecular Spectroscopy and Reactions of Actinides in the Gas Phase and Cryogenic Matrices (Michael C. Heaven, John K. Gibson, and Joaquim Marçalo) 39. Hydrothermal Synthesis and Crystal Structures of Actinide Compounds (Thomas E. Albrecht-Schmitt, Peter C. Burns, and Sergey V. Krivovichev).
Electronic reproduction.
Keywords: Actinide elements; Transuranium elements; Superheavy elements; Electronic books